The School and Cultural Diversity: Notes on Multicultural Education in Portugal - Almeida, José Carlos Pina (Education Policy Analysis Archives, 2006)
Multiculturalism, as a political project, has captured much attention in recent decades. Multicultural education, in particular, has been often viewed as the ideal way to facilitate interaction between cultures and to achieve more effective equality of opportunities and, therefore, a fairer society. But it has also been involved in much controversy. We start this article by reviewing some of the debates around the multicultural paradigm. We will then turn our attention to the Portuguese case. In particular we will explore the way the view of the Portuguese history and culture as a humanist, universalist and non-racist one, has influenced the way the education system deals with the growing cultural diversity in the Portuguese society.